Maritime Examinations Scheduled - Los Angeles Examiner (Los Angeles Examiner)
Competitive entrance examinations for admission to the California Maritime Academy for youths from 17 to 23 who wish to serve in the Merchant Marine will be held on or about May 5 in Los Angeles and San Francisco .